Ozbrojené konflikty po konci studené války. - Pospíšil, Ivo (Masarykova univerzita, 2012)
Did the end of the Cold War represent any kind of fundamental milestone in armed conflicts? Answering this question became the central research focus the presented book. The book is divided into two topical parts. The first part provides an introduction to armed conflicts and introduces the reader to the fundamental terminology and typology in this particular field (Petr Suchý). Further chapters reflect armed conflicts in theories of international relations (Pavel Pšeja, Zuzana Vránová) and specifically focus on the conceptual changes surrounding a "just war"--Bellum iustum (Eva Duřpektová).